MALE DOMINANCE AND INTIMATE PARTNER VIOLENCE AGAINST WOMEN IN BENUE STATE NIGERIA - Ahingir, Terfa Matthew; Eke, Chijioke Chinwokwu (African Journal of Social and Behavioural Sciences, 2025)
Intimate Partner Violence (IPV) is a global issue with severe consequences on an individual`s physical, mental, sexual and social well-being. Despite the fact that it affects individuals across races, religions, and social classes, it is often condoned in most societies. The continuous incidences of violence against women have affected their health and their ability to be productive in the family and community. This situation thrives due to socio-cultural norms that tolerate and entrench violence against women. The study examined how male dominance engendered intimate partner violence against women. Specifically, the study explored male control and household decision-making and IPV in Benue State, Nigeria. A cross-sectional survey design with a sample size of 660 was utilised. Data was collected through Structured Questionnaires and a Key Informant Interviews Guide. Quantitative data was processed using Statistical Package for Social Sciences (SPSS) version 23, and qualitative data was transcribed and thematically organised. The study found that male dominance influences intimate partner violence against women due its entrenched patriarchal power imbalances, control and household decision-making. The study recommended that traditional leaders should lead the charge in transforming cultural beliefs such as male dominance that perpetuate inequality; by fostering a culture of mutual respect, collaborative decision-making and equal opportunities for all. Also, joint decision-making must be promoted by involving women in household decision-making processes.